Adaptation and Validation of a Four-Tier Misconception Diagnostic Test on Work and Energy Using Rasch Modeling - Gress Faihah; Moh. Irma Sukarelawan; Toni Kus Indratno (Jurnal Ilmiah Pendidikan Fisika, 2025)
The WPECT instrument has been globally tested for its quality in diagnosing student misconceptions. However, this instrument cannot be directly used in the Indonesian cultural context due to language differences. Therefore, a cross-cultural adaptation process is required. This study aims to adapt and cross-culturally validate a four-tier diagnostic test on the concepts of Work, Power, and Energy using the Rasch model (1PL) based on item difficulty estimation. The research was conducted using a quantitative survey method involving 125 students from SMA Negeri 1 Jetis. The focus of the study is to adapt and validate the 4-tier Work, Power, and Energy instrument to the Indonesian context. The analysis results show that the item reliability index is 0.87 and the Cronbach's Alpha is 0.81, indicating a high level of internal consistency within the instrument. The distribution of item difficulty is spread across four categories, with the majority of items classified as difficult. Twelve out of thirteen items meet the Rasch model fit criteria, while one item can still be retained as its outfit MNSQ value remains below the acceptable threshold (< 2.0). The instrument also fulfills the assumption of unidimensionality, as all 13 items measure a single underlying construct—namely, the concept of work, power, and energy. Furthermore, no gender-based item bias was detected. Therefore, the four-tier diagnostic test on the topic of work and energy is suitable for identifying misconceptions among high school students in Indonesia, validly and equitably. The availability of this adapted instrument can help educators in Indonesia more accurately diagnose student misconceptions and design more targeted instructional interventions.